1973
DOI: 10.2118/3788-pa
|View full text |Cite
|
Sign up to set email alerts
|

Determining Residual Oil Saturation Behind a Waterflood-A Case History

Abstract: Thorough analysis of cores and logs from a well drilled behind a waterflood in a permeable sand indicates a residual oil saturation, under reservoir conditions, of not more than 25 percent, and possibly as low as 20 percent. This is in good agreement with laboratory flood tests of cores. Introduction and Background Actual cumulative oil production from a sandstone reservoir subjected to waterflood has fallen significantly short of that predicted by experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Hence, oil remaining in place as a target for tertiary recovery may be much less than what was estimated by conventional methods of determining porosity and subtracting cumulative oil production. Later Elkins and Poppe (1973) evaluated a field case to estimate the residual oil saturation left for the tertiary oil recovery. They reported that the reduction in porosity due to compaction should be recognized and pressure coring is important in the evaluation of unconsolidated field cases.…”
Section: Field Experiencesmentioning
confidence: 99%
“…Hence, oil remaining in place as a target for tertiary recovery may be much less than what was estimated by conventional methods of determining porosity and subtracting cumulative oil production. Later Elkins and Poppe (1973) evaluated a field case to estimate the residual oil saturation left for the tertiary oil recovery. They reported that the reduction in porosity due to compaction should be recognized and pressure coring is important in the evaluation of unconsolidated field cases.…”
Section: Field Experiencesmentioning
confidence: 99%
“…1. S orw = 24.0 percent, determined from core analysis and well logs, the field was not defined (Elkins and Poppe, 1973).…”
Section: Sandstone Reservoirsmentioning
confidence: 99%
“…This increased the calculated oil recovery efficiency from 35 to 55% of oil in place. 20 Essentially every factor affecting porosity and water saturation discussed here tends to overcalculate oil in place unless it is properly considered.…”
Section: Alternative Interpretationsmentioning
confidence: 99%